Senior citizen tourism - the target group of old age pensioners in hospitality industry and tourist companies - Ginevičius, Romualdas; Hausmann, Thomas; Schafir, Schlomo (Business: Theory and Practice, 2007)
Marketing glowingly deals with the social stratum of senior citizens as a target group. The potentially enterprising, elderly guests with much money to spend are increasingly addressed by advertisements. But this potential is not easy to win. Also tourism has to be prepared for the requirements of elderly people. Nevertheless, senior citizens can be seen as a growing market in tourism, which is proved by the assay available. Study trips, educational holidays and cultural trips are especially popular with senior citizens.Article in German.Seniorentourismus – die Zielgruppe Senioren in Gastgewerbe und TouristikAuszug. Das Marketing beschäftigt sich zunehmend mit der älteren Bevölkerungsschicht als Zielgruppe. Die kaufkräftigen und unternehmungslustigen (potentiellen) älteren Gäste werden z.B. durch Werbung vermehrt angesprochen. Dieses Potential ist jedoch nicht so einfach zu gewinnen. Auch der Tourismus hat sich auf die heterogenen Ansprüche der älteren Menschen einzurichten. Nichts desto trotz sind Senioren als Wachstumsmarkt im Tourismus zu sehen, was der vorliegende Aufsatz beweist. Besonders beliebt bei Senioren sind Studien-, Bildungs- und Kulturreisen.Schlusselworter: Seniorentourismus, Wachstumspotental des seniorenmarktes, Kernzielgruppe im Tourismusmarkt, demografische Entwicklung, Sozio - ökonomische und psychografische Faktoren, Reiseverhalten der Senioren.